A Facile Ionic Liquid Promoted Synthesis, Cholinesterase Inhibitory Activity and Molecular Modeling Study of Novel Highly Functionalized Spiropyrrolidines - I. Almansour, Abdulrahman; Kumar, Raju Suresh; Arumugam, Natarajan; Basiri, Alireza; Kia, Yalda; Ali, Mohamed Ashraf; Farooq, Mehvish; Murugaiyah, Vikneswaran (MDPI, 2015)
A series of novel dimethoxyindanone embedded spiropyrrolidines were synthesized in ionic liquid, [bmim]Br and were evaluated for their inhibitory activities towards cholinesterases. Among the spiropyrrolidines, compound 4f exhibited the most potent activity with an IC50 value of 1.57 μM against acethylcholinesterase (AChE). Molecular docking simulation for the most active compound was employed with the aim of disclosing its binding mechanism to the active site of AChE receptor.